A Novel Multi-Preprocessing Integration Method for the Qualitative and Quantitative Assessment of Wild Medicinal Plants: Gentiana rigescens as an Example - Liu, Zhimin; Shen, Tao; Zhang, Ji; Li, Zhimin; Zhao, Yanli; Zuo, Zhitian; Zhang, Jinyu; Wang, Yuanzhong (Frontiers in Plant Science, 2021)
Until now, the over-exploitation of wild resources has increased growing concern over the quality of wild medicinal plants. This led to the necessity of developing a rapid method for the evaluation of wild medicinal plants. In this study, the content of total secoiridoids (gentiopicroside, swertiamarin, and sweroside) of Gentiana rigescens from 37 different regions in southwest China were analyzed by high performance liquid chromatography (HPLC). Furthermore, FT-IR was adopted to trace the geographical origin (331 individuals) and predict the content of total secoiridoids (273 individuals). In the traditional FT-IR analysis, only one scatter correction technique could be selected from a series of pre-processing candidates to decrease the impact of the light correcting effect. Nevertheless, different scatter correction techniques may carry complementary information so that, using the single scatter correction technique is sub-optimal. Hence, the emerging ensemble approach to pre-processing fusion, sequential preprocessing through orthogonalization (SPORT), was carried out to fuse the complementary information linked to different pre-processing methods. The results suggested that compared with the best results obtained on the scatter correction modeling, SPORT increased the accuracy of the test set by 12.8% in qualitative analysis and decreased the RMSEP by 66.7% in quantitative analysis.